Early childhood education and care in a context of social heterogeneity and inequality. Empirical notes on an interdisciplinary challenge. Issue 1 (2nd January 2016) - Schoyerer, Gabriel; van Santen, Eric
Abstract : Against a background of increasing inequality and its impact at various levels on childhood and family life, of the growing societal significance and uptake of extra-familial childcare provision, and of social policy goals emphasising participation and education for all, the early childhood education and care (ECEC) sector in Germany is facing new and heightened challenges. This article presents and analyses current and empirically observable changes in society. It comes to the conclusion that ECEC needs to be more strongly viewed as an interdisciplinary challenge, and that ways forward need to include a comprehensive professionalisation and workforce development project: the aim must be to provide children and families with care and support services tailored both quantitatively and qualitatively to their needs, thereby offering not only support to facilitate the reconciliation of work and family obligations and an alternative place of education for children, but also programmes of specific support for disadvantaged and support-dependent children and families.